SPE Annual Technical Conference and Exhibition 2016
DOI: 10.2118/181346-ms
|View full text |Cite
|
Sign up to set email alerts
|

To the Barricades! Using a Self-Assembled Wall to Protect Ordinary Portland Cement from Acidic Corrosion

Abstract: A novel cement additive, capable of creating an insoluble barrier at the first sign of acid attack, is offered. When present in small quantities, it allows ordinary Portland cement (OPC) to protect itself from acid corrosion as shown by laboratory tests. This corrosion resistance is critical especially in regards to attack from carbonic acid produced when CO2 combines with water or from naturally occurring H2S in the well. These acids can turn OPC porous and weak, rendering it incapable of maintaining zonal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It showed that conventional Portland cement had a compressive strength decrease of 21.43%, while calcium-aluminate cement was only 5.16%. In addition, weight control agents, such as fly ash, , slag, , nanoparticles (e.g., microsilicon), , resins, , polymers, and many other swelling agents , can be added to adjust the CaO percentage, improve the cement density, and obtain better cement strength. In recent years, there have been many CO 2 -resistant additives developed to protect conventional Portland cement from acidic corrosion. Vorderbuggen et al and Doan et al developed a cement additive (e.g., hydroxyethylcellulose, methyl hydroxyethylcellulose, and carboxymethyl hydroxyethyl cellulose) that can create an insoluble barrier when it encounters an acid attack. Laboratory tests showed that this additive performed well under specific pressure and temperature in brines saturated with CO 2 for weeks.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed that conventional Portland cement had a compressive strength decrease of 21.43%, while calcium-aluminate cement was only 5.16%. In addition, weight control agents, such as fly ash, , slag, , nanoparticles (e.g., microsilicon), , resins, , polymers, and many other swelling agents , can be added to adjust the CaO percentage, improve the cement density, and obtain better cement strength. In recent years, there have been many CO 2 -resistant additives developed to protect conventional Portland cement from acidic corrosion. Vorderbuggen et al and Doan et al developed a cement additive (e.g., hydroxyethylcellulose, methyl hydroxyethylcellulose, and carboxymethyl hydroxyethyl cellulose) that can create an insoluble barrier when it encounters an acid attack. Laboratory tests showed that this additive performed well under specific pressure and temperature in brines saturated with CO 2 for weeks.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
“…In recent years, there have been many CO 2 -resistant additives developed to protect conventional Portland cement from acidic corrosion. Vorderbuggen et al and Doan et al developed a cement additive (e.g., hydroxyethylcellulose, methyl hydroxyethylcellulose, and carboxymethyl hydroxyethyl cellulose) that can create an insoluble barrier when it encounters an acid attack. Laboratory tests showed that this additive performed well under specific pressure and temperature in brines saturated with CO 2 for weeks.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%